Optimalisasi Fungsi Desa Adat dalam Tata Kelola Lingkungan Berkelanjutan di Desa Tenganan Pegringsingan Karangasem: Pengabdian - Bagus Gede Ari Rama; Ni Nyoman Juwita Arsawati; I Gede Agus Kurniawan; Kadek Julia Mahadewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sustainable environmental management in Tenganan Pegringsingan Indigenous Village reflects harmony between local wisdom, environmental preservation, and ecotourism development. This village preserves the Bali Aga tradition, which upholds customary values in protecting nature, such as the awig-awig system and the Tri Hita Karana philosophy. The local community practices conservation by limiting natural resource use, prohibiting harmful chemicals, and protecting forests and water sources. Ecotourism is developed participatively and sustainably, emphasizing community involvement, cultural integrity, and minimal environmental impact. Through this community service activity, assistance was provided to strengthen local capacity, enhance community awareness of environmental management, and identify potential tourism based on culture and nature. This collaborative approach, integrating customary values and academic knowledge, demonstrates that local wisdom can serve as a fundamental basis for supporting the Sustainable Development Goals (SDGs), particularly in environmental conservation and community empowerment.